Electrolyte Concentration Effect of a Photoelectrochemical Cell Consisting of TiO2 Nanotube Anode. (20th March 2013) - Ren, Kai; Gan, Yong X.; Nikolaidis, Efstratios; Sofyani, Sharaf Al; Zhang, Lihua
Abstract : The photoelectrochemical responses of a TiO2 nanotube anode in ethylene glycol (EG), glycerol, ammonia, ethanol, urea, and Na2 S electrolytes with different concentrations were investigated. The TiO2 nanotube anode was highly efficient in photoelectrocatalysis in these solutions under UV light illumination. The photocurrent density is obviously affected by the concentration change. Na2 S generated the highest photocurrent density at 0, 1, and 2 V bias voltages, but its concentration does not significantly affect the photocurrent density. Urea shows high open circuit voltage at proper concentration and low photocurrent at different concentrations. Externally applied bias voltage is also an important factor that changes the photoelectrochemical reaction process. In view of the open circuit voltage, EG, ammonia, and ethanol fuel cells show the trend that the open circuit voltage (OCV) increases with the increase of the concentration of the solutions. Glycerol has the highest OCV compared with others, and it deceases with the increase in the concentration because of the high viscosity. The OCV of the urea and Na2 S solutions did not show obvious concentration effect.